2004 IEEE 15th International Symposium on Personal, Indoor and Mobile Radio Communications (IEEE Cat. No.04TH8754)
DOI: 10.1109/pimrc.2004.1368399
|View full text |Cite
|
Sign up to set email alerts
|

High data rate enhancement for beyond 3G services using complete complementary codes

Abstract: In this paper, we present a Multiple-InputMultiple-Output (MIMO) Code-Division-Multiple-Access (CDMA) communication system based on Complete Complementary (CC) codes (CC-CDMA) in a timedispersive (i.e. frequency-selective fading) channel. This system utilizes a novel combination, which consists of orthogonal CC codes for data spreading and a suitably designed Multi-User-Detector (MUD) algoaithm, in order to enhance the current 3rd Generation (3G) mobile systems. The simulation results for the CC-CDMA system, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Walsh code, the BER performance would degrade badly when number of users is increased, and the curves of BER v.s. SNR reveal 'platform phenomenon' [6]. It can be concluded that the performance gain of the proposed system is obvious in multi-user, frequency-selective fading channel conditions.…”
Section: Simulation Results and Analysismentioning
confidence: 83%
See 3 more Smart Citations
“…Walsh code, the BER performance would degrade badly when number of users is increased, and the curves of BER v.s. SNR reveal 'platform phenomenon' [6]. It can be concluded that the performance gain of the proposed system is obvious in multi-user, frequency-selective fading channel conditions.…”
Section: Simulation Results and Analysismentioning
confidence: 83%
“…Hence the fading-resist ability of the proposed system is stronger than that of the MIMO CC-CDMA [6] utilizing only the first path component for data decision. Third, the system can provide both high data rate and low hardware complexity.…”
Section: Propertiesmentioning
confidence: 94%
See 2 more Smart Citations